Malignant melanoma of inner canthus with long‐term survival after resection of brain metastasis and treatment with ipilimumab. Issue 1 (15th July 2022) - Yasuda, Masahito; Uehara, Akihito; Saito, Shintaro; Kuriyama, Yuko; Yamada, Kazuya; Oka, Aina; Miyagawa, Marie; Ishikawa, Osamu; Motegi, Sei‐Ichiro
Abstract : Cerebellar metastasis from malignant melanoma of the inner canthus was resected. The patient was subsequently treated with ipilimumab and has remained disease‐free 6 years, however, developed sarcoidosis.